Epidemiology and prediction model of patients with carcinosarcoma in the United States - Chen, Mingjing; He, Xiandong; Yang, Qiao; Zhang, Jia; Peng, Jiayi; Wang, Danni; Tong, Kexin; Huang, Wenxiang (Frontiers in Public Health, 2022)
Background Carcinosarcoma is a rare biphasic tumor composed of both carcinoma and sarcoma elements, which occurs at various sites. Most studies are case reports or small population-based studies for a single disease site, so comprehensive evaluations of epidemiology and prognostic factors for carcinosarcoma are needed. Methods Surveillance, Epidemiology, and End Results (SEER)-8 (1975–2019) provided data for the epidemiological analysis. SEER-17 (2000–2019) provided data on the primary tumor sites, initial treatment, construction, and validation of the nomogram. Results The age-adjusted incidence per 100,000 persons of carcinosarcoma increased significantly from 0.46 to 0.91 [1975–2019; average annual percent change (AAPC): 1.3%, P = 0.006], with localized stage increasing from 0.14 to 0.26 [2005–2015; annual percent change (APC): 4.2%]. The 20-year limited-duration prevalence per 100,000 increased from 0.47 to 3.36 (1999–2018). The mortality per 100,000 increased significantly from 0.16 to 0.51 (1975–2019; AAPC: 1.9%, P < 0.001). The 5-year relative survival was 32.8%. The greatest number of carcinosarcomas were from the uterus (68.7%), ovary (17.8%), lung and bronchus (2.3%). The main treatment is comprehensive treatment based on surgery; however, surgery alone is preferred in older patients. In multivariate analysis (N = 11,424), age, sex, race, year of diagnosis, disease stage, tumor site, and treatment were associated with survival. A nomogram was established to predict 1-, 3-, and 5-year survival, and the C-indexes were 0.732 and 0.748 for the training and testing sets, respectively. The receiver operating characteristic curve demonstrated that the nomogram provided a comprehensive and accurate prediction [1-year area under the curve (AUC): 0.782 vs. 0.796; 3-year AUC: 0.771 vs. 0.798; 5-year AUC: 0.777 vs. 0.810]. Conclusions In this study, the incidence, prevalence, and mortality of carcinosarcoma have increased over the past decades. There was a rapid rise in the incidence of localized stage in recent years, which reflected improved early detection. The prognosis of carcinosarcoma remains poor, signifying the urgency of exploring targeted cancer control treatments. Explicating distribution and gender disparities of carcinosarcoma may facilitate disease screening and medical surveillance. The nomogram demonstrated good predictive capacity and facilitated clinical decision-making.